Sparsh Glove: A Gesture-Based Hardware Control for a Multipurpose Wheelchair - Siri T, Bhat; Surekha, B; Raghavan, Shreesha (International Journal of Computer Sciences and Engineering, 2025)
The problems of locomotion exist not only for the aged, but also for the physically challenged, who might still be in the prime of their youth. The earlier versions of the wheelchair demand much of the manual effort to move the wheelchair. This paper presents a Sparsh Glove control system, aiming to resolve these issues, by allowing the user to control a wheelchair using natural gestures. The Sparsh Glove takes advantage of a multitude of sensors to capture hand movements and uses this information to control a wheelchair which also has provisions for seat elevation and various other features. Further, the wheelchair is designed to warn the user whenever there is an obstacle in the path of the wheel, and if there is any obstruction behind the user.